1966
DOI: 10.1136/bmj.2.5520.967
|View full text |Cite
|
Sign up to set email alerts
|

Special problems of the aged and the organization of hospital services.

Abstract: The illnesses and disabilities of ageing have during the past two decades loomed increasingly large among the problems faced by health and welfare services in economically advanced countries. In recent years a number of surveys have helped to define the extent of the problem. In Newcastle upon Tyne, for example (Kay, Beamish, and Roth, 1964)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…In N. Ireland as a whole corresponding figures were 47.1% of males and 41.7% of females, representing 4/1000 and 3.4/1000 respectively of the population at risk. These figures agree fairly closely with those provided by Kay, Roth and Hall (1966). In the mental hospitals in Newcastle 'half of the recently admitted geriatric patients suffered from essentially irreversible arteriosclerotic or senile degeneration while 28% were disabled from a physical disease'.…”
Section: (B)supporting
confidence: 80%
“…In N. Ireland as a whole corresponding figures were 47.1% of males and 41.7% of females, representing 4/1000 and 3.4/1000 respectively of the population at risk. These figures agree fairly closely with those provided by Kay, Roth and Hall (1966). In the mental hospitals in Newcastle 'half of the recently admitted geriatric patients suffered from essentially irreversible arteriosclerotic or senile degeneration while 28% were disabled from a physical disease'.…”
Section: (B)supporting
confidence: 80%
“…Psycho-geriatric assessment units, initially proposed in 1950 47 had largely failed to become widespread. Nor did they fl ourish after their reiteration in 1970 (DHSS), a response to WHO's suggestions (1959) and an infl uential paper by Kay, Roth and Hall (1966) and Kidd's study (1962) -later shown to be fl awed (Copeland et al, 1975) -stressing poorer prognosis for older people placed in the wrong type of unit. Thus psycho-geriatric units aimed to ensure accurate assessment of elderly patients with complex problems, but were never of proven value .…”
Section: Collaboration and Dissent: Working With Geriatriciansmentioning
confidence: 99%
“…There was less focus on the possibility of psychiatric day assessment, such units existing in only a few places such as at Exminster in Devon (DHSS, 1971;Kay et al, 1966;Langley, Wright, Sowden and Cobby, 1975). Older people were unlikely to be admitted to general psychiatry day hospitals, and many geriatric day hospitals seemed also to exclude the demented.…”
Section: The Day Hospitalmentioning
confidence: 99%
“…Obviously this is more likely to happen if the patient lives alone. The answer to this problem is not easy -it has been suggested (Kay et al, 1966) that there should be a system of registration by local authorities of old people living alone and that regular visiting should be introduced so that any deterioration can be identified in the early stages. This should be combined with the provision of domiciliary services of various kinds, such as clubs, day centres or day hospitals.…”
Section: (B) Illnesses Associated With Age Itselfmentioning
confidence: 99%